Dari Pola Budaya menuju Pemahaman Bilangan Rasional: Pemanfaatan Etnomatematika Tapis Lampung untuk Mendukung Pembelajaran Pecahan dan Desimal di Kelas 6 - Dewi Yusanti; Amalia Sapriati (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
This study describes the implementation of ethnomathematics-based mathematics instruction using Tapis Lampung to strengthen sixth-grade students’ understanding of fractions and decimals at SD Negeri 51 Krui. Grounded in ethnomathematics, culturally responsive pedagogy, and representation-rich instruction, the study used a one-cycle classroom action research design involving 39 students in three meetings on 8, 15, and 22 April 2025. Data were obtained from pretests, posttests, observations, worksheets, group projects, field notes, and teacher reflections. The intervention introduced the cultural meaning of Tapis, explored part-whole relationships in its motifs, guided students in converting fractions into decimals, and ended with collaborative presentations. Results show that Tapis motifs helped students visualize fractions, understand decimal representation, enrich mathematical discussion, and appreciate local culture. Mean scores rose from 58.46 to 78.72, learning mastery increased from 38.46% to 82.05%, and the N-gain reached 0.49 (moderate).